Development and Implementation of Portable Ultrasonic Sensor Circuit with USB Interface and Signal Processing to Detect Damages in the Mild Steel Structure - Shrestha, Manish Man; Ropakheti, Bibek; Bhattarai, Uddhav; Shakya, Amit (Advances in Engineering and Technology: An International Journal, 2022)
Mild steel is one of the widely used structures for commercial use. In this paper, we present a PZT-based portable ultrasonic wave interfacing circuit with a USB interface to detect the damages in the mild steel structure. The designed circuit amplifies and shifts the level of the ultrasonic waves. The wave is then digitized by the microcontroller with a sampling rate of 2 MHz. The digitized wave is then transferred to the PC via USB communication. The CDC class was used in USB communication to generate a virtual com port and capture the data in real-time. The wave was then filtered and processed in the PC to detect damage to the structure. The dimension and weight of the used mild steel are 570mm x 205mm x 10mm and 10 kg respectively. To detect the damage to the structure, the 200 kHz tone-burst signal was induced in it through the PZT actuator. The ultrasonic wave was then captured in both intact and damaged conditions of the structure. The induced damage was of dimension 1mm x 10mm x 5mm. The RMS value of the captured wave in intact condition and the undamaged condition was calculated. This run-in of the RMS values in the intact and damaged condition of the structure solidifies the capability of the device to gather the ultrasonic wave correctly.